Compositional Features and Bioactive Properties of Aloe vera Leaf (Fillet, Mucilage, and Rind) and Flower - Mikel Añibarro-Ortega; José Pinela; Lillian Barros; Ana Ćirić; Soraia P. Silva; Elisabete Coelho; Andrei Mocan; Ricardo C. Calhelha; Marina Soković; Manuel A. Coimbra; Isabel C. F. R. Ferreira (MDPI AG, 2019)
This work aimed to characterize compositional and bioactive features of Aloe vera leaf (fillet, mucilage, and rind) and flower. The edible fillet was analysed for its nutritional value, and all samples were studied for phenolic composition and antioxidant, anti-inflammatory, antimicrobial, tyrosinase inhibition, and cytotoxic activities. Dietary fibre (mainly mannan) and available carbohydrates (mainly free glucose and fructose) were abundant macronutrients in fillet, which also contained high amounts of malic acid (5.75 g/100 g dw) and α-tocopherol (4.8 mg/100 g dw). The leaf samples presented similar phenolic profiles, with predominance of chromones and anthrones, and the highest contents were found in mucilage (131 mg/g) and rind (105 mg/g) extracts, which also revealed interesting antioxidant properties. On the other hand, the flower extract was rich in apigenin glycoside derivatives (4.48 mg/g), effective against Pseudomonas aeruginosa (MIC = 0.025 mg/mL and MBC = 0.05 mg/mL) and capable of inhibiting the tyrosinase activity (IC50 = 4.85 mg/mL). The fillet, rind, and flower extracts also showed a powerful antifungal activity against Aspergillus flavus, A. niger, Penicillium funiculosum, and Candida albicans, higher than that of ketoconazole. Thus, the studied Aloe vera samples displayed high potential to be exploited by the food or cosmetic industries, among others.